Microbial Functional Diversity in Vineyard Soils: Sulfur Metabolism and Links With Grapevine Plants and Wine Quality - Mocali, Stefano; Kuramae, Eiko E.; Kowalchuk, George A.; Fornasier, Flavio; Priori, Simone (Frontiers in Environmental Science, 2020)
The quality of the vineyard soils has a direct impact on grapes and wine quality and represents a key component of the “Terroir concept.” However, information on the impact of soil microbiota on grapevine plants and wine quality are generally lacking. In fact, over the last few years most of the attempts made to correlate soil microbial communities and wine quality were limited by overlooking both the functional traits of soil microbiota and the spatial variability of vineyards soils. In this work, we used a functional gene microarray approach (GeoChip) and soil enzymatic analyses to assess the soil microbial community functional potential related to the different wine quality. In order to minimize the soil variability, this work was conducted at a “within-vineyard” scale, comparing two similar soils (BRO11 and BRO12) previously identified with respect to pedological and hydrological properties within a single vineyard in Central Tuscany and that yielded highly contrasting wine quality upon cultivation of the same Sangiovese cultivar (BRO12 exhibited the higher quality). Our results showed an enrichment of Actinobacteria in BRO12, whereas Alfa- and Gamma-Proteobacteria were more abundant in BRO11, where an enrichment of bacteria involved in N fixation and denitrification occurred. Overall, the GeoChip output revealed a greater biological activity in BRO11 but a significant enrichment of sulfur-oxidation genes in BRO12 compared to BRO11 soil, where a higher level of arylsulfatase activity was also detected. Moreover, the low content of sulfates and available nitrogen found in BRO12 suggested that the reduced availability of sulfates for vine plants might limit the reduced glutathione (GSH) synthesis, which plays an important role in aroma protection in musts and wines. In conclusion, in addition to nitrogen availability, we propose that soil microbial sulfur metabolism may also play a key role in shaping plant physiology, grapes and wine quality. Overall, these results support the existence of a “microbial functional terroir” effect as a determining factor in vineyard-scale variation among wine grapes.